Analysis of hemodynamic changes from aneurysm inception to large sizes. (25th November 2020) - Salimi Ashkezari, Seyedeh Fatemeh; Mut, Fernando; Chung, Bong Jae; Robertson, Anne M.; Frösen, Juhana; Cebral, Juan R.
Abstract: While previous studies have identified many risk factors for the progression and rupture of cerebral aneurysms, the changes in aneurysm flow characteristics during its evolution are not fully understood. This work analyzes the changes in the aneurysm hemodynamic environment from its initial development to later stages when the aneurysm has substantially enlarged. A total of 88 aneurysms at four locations were studied with image based computational fluid dynamics (CFD). Two synthetic sequences representing the aneurysm geometry at three earlier stages were generated by shrinking the aneurysm sac while keeping the neck fixed or shrinking the neck simultaneously. The flow conditions were then quantitatively compared between these two modes of evolution. As aneurysms enlarged, the inflow rate increased in growing neck sequences, but decreased in fixed neck sequences. The inflow jet became more concentrated in both sequences. The mean aneurysm flow velocity and wall shear stress decreased in both sequences, but they decreased faster in enlarging aneurysms if the neck was fixed. Additionally, the intra‐aneurysmal flows became more complex and more unstable, wall shear stress distribution became more oscillatory, and the area under low wall shear stress increased for both sequences. The evolution of flow characteristics of aneurysms with fixed and growing necks are different. The observed trends suggest that fixed neck aneurysms may evolve towards a flow environment characteristic of stable aneurysms faster than aneurysms with growing necks, which could also evolve towards a more disfavorable environment. Abstract : The evolution of flow characteristics of aneurysms with fixed and growing necks are different. As the aneurysms enlarges, the mean flow velocity and wall shear stress decrease, while the flow complexity, instability, and oscillation increase. Additionally, the inflow rate increases in aneurysms with growing necks and the inflow jet becomes more concentrated as the aneurysm enlarges. These observations suggest that fixed neck aneurysms may evolve towards a flow environment characteristic of stable aneurysms faster than aneurysms with growing necks.